2019
DOI: 10.3389/fgene.2019.00039
|View full text |Cite
|
Sign up to set email alerts
|

FBXL4-Related Mitochondrial DNA Depletion Syndrome 13 (MTDPS13): A Case Report With a Comprehensive Mutation Review

Abstract: Mitochondrial DNA depletion syndromes (MTDPS) are a group of rare genetic disorders caused by defects in multiple genes involved in mitochondrial DNA (mtDNA) maintenance. Among those, FBXL4 mutations result in the encephalomyopathic mtDNA depletion syndrome 13 (MTDPS13; OMIM #615471), which commonly presents as a combination of failure to thrive, neurodevelopmental delays, encephalopathy, hypotonia, and persistent lactic acidosis. We report here the case of a Lebanese infant presenting to us with profound neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…The present case was similar in presentation with Bonnen et al but cardiomyopathy, signs, sensory-neuronal hearing impairment, cataract and optic atrophy were preserved [1]. On the other hand, expected survival time was extended more than infancy and had lower complications (anemia, leukopenia and hypoalbuminemia) like the case reported by Ballout et al (Table 3) [6]. This emphasizes the remarkable variability in genotype-tophenotype correlation characteristic of this disease.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present case was similar in presentation with Bonnen et al but cardiomyopathy, signs, sensory-neuronal hearing impairment, cataract and optic atrophy were preserved [1]. On the other hand, expected survival time was extended more than infancy and had lower complications (anemia, leukopenia and hypoalbuminemia) like the case reported by Ballout et al (Table 3) [6]. This emphasizes the remarkable variability in genotype-tophenotype correlation characteristic of this disease.…”
Section: Discussionsupporting
confidence: 87%
“…Among those is FBXL4 mutation. To the best of author's knowledge, this patient represented the 95 th case of Mitochondrial DNA Depletion Syndrome 13 (MTDPS13) related to pathogenic mutation in FBXL4 in a 3 years old Saudi girl worldwide [6]. Majority of this genotype were presented at birth with lactic acidosis, severe hypotonia, encephalopathy, epilepsy, kyphosis/scoliosis, cardiomyopathy, poor neurodevelopmental outcome, growth retardation, mildly craniofacial dysmorphic features, and mortality during infancy [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FBXL4 is considered to participate in oxidative phosphorylation, mitochondrial dynamics, cell migration, prostate cancer metastasis, circadian GABAergic cyclic alteration, etc. [35][36][37][38][39]. The association results in pigs found that blood and immune traits were associated with the SNPs of FBXL4 [40].…”
Section: Gene and Metabolite Interaction Networkmentioning
confidence: 98%
“…Skeletal muscle commonly shows mitochondrial dysfunctions with combined deficiencies of multiple OXPHOS complexes and mtDNA depletion. Patient’s fibroblasts typically display fragmented mitochondria and combined deficiencies of multiple OXPHOS complexes [ 98 , 99 , 100 , 101 , 130 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ].…”
Section: Mitochondrial Dynamics Related Disordersmentioning
confidence: 99%